2020
DOI: 10.6087/kcse.212
|View full text |Cite|
|
Sign up to set email alerts
|

Bibliometric analysis of flipped classroom publications from the Web of Science Core Collection published from 2000 to 2019

Abstract: Purpose: This study analyzed the bibliometric characteristics of flipped classroom publications in the Social Science Citation Index and Science Citation Index Expanded from 2000 to 2019. Methods: The terms related to “flipped classroom” and “inverted learning” were the keywords for searching journal articles on January 3, 2020. Results: There are 645 articles (including 33 early-access articles), representing 1,938 authors in the 210 journals scanned. The United States, China, and Taiwan were three leading co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
1
7
0
3
Order By: Relevance
“…From the study period, the number of publications grew steadily in the sources analysed, this finding is in analogy with what [29], [31], [32] expounded. It starts 2012 with only one publication up to 152 documents in the year 2020 (October), this shows that FC research in higher education is in growing development.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…From the study period, the number of publications grew steadily in the sources analysed, this finding is in analogy with what [29], [31], [32] expounded. It starts 2012 with only one publication up to 152 documents in the year 2020 (October), this shows that FC research in higher education is in growing development.…”
Section: Discussionsupporting
confidence: 67%
“…There are previous bibliometric studies related to FC in general [29]- [32]. Their works were oriented to analyzing the growth of scientific production on FC, productivity according to countries, thematic categories, journals, frequency of keywords, impact through citations and bibliometric networks of the analyzed documents.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Scopus database, only a small number of authors have published their work on the flipped classroom in EFL. Out of all authors who have published their works, only Abdullah, et.al This research results are supported by a bibliometric analysis conducted by Tsai & Wu (2020). They found that there are 645 articles focused on flipped-classroom across multiple disciplines based on data taken from Web of Science.…”
Section: Most Active Authorsmentioning
confidence: 62%
“…al., 2019;Keengwe et al, 2014;Oncel & Kara, 2019). Through this process, teachers are required to deliver pre-recorded class lectures and course materials online before the class, so that face-to-face contact is dedicated to collaborative group discussions and extensive problem solving (Mok, 2014;Oncel & Kara, 2019;Tsai & Wu, 2020). Research shows many benefits of the flipped learning approach such as increased learning outcomes (L. Jang & Kim, 2020), effective projectbased teaching (P. W. , positive student attitude (Kang, 2015), improved teacher-student and student-student interaction and active learning (Della Ratta, 2015), meta-cognition (Van Vliet et al, 2015), problem solving (Chun & Lee, 2016), and student engagement (Jang & Kim, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although, Karabulut-Ilgu et al (2018) systematically reviewed the use of the flipped learning method in engineering education, it provides only a qualitative synthesis of previous studies. Furthermore, Tsai and Wu (2020) recently performed a bibliometric analysis but it is lacking a review of the status of flipped learning research in engineering education. Therefore, no existing research studies have objectively studied the developments in flipped learning research within engineering education.…”
Section: Introductionmentioning
confidence: 99%